Treatment of chronic isolated distal tibiofibular syndesmosis injury. Literature update and case report using autologous semitendinous graft reconstruction - Pagliari, Micaela; Giardini, Piero; Rosà, Livio; Menna, Carlo Raimondo; Christodoulidis, Avraam; Molinari, Marco (Lo Scalpello - Journal, 2021)
Isolated distal tibiofibular syndesmosis lesions are rare and can be easily missed. Diagnosis and treatment of chronic disruption is not easy, with limited published data. Surgical treatment of chronic syndesmosis injury is challenging as there is no international consensus on the optimal management. Diagnosis and treatment are still controversial and poorly discussed in literature. PubMed/Medline, Cochrane Database of Systematic Reviews, Cochrane Clinical Trial Register, Current Controlled Trials and Embase were searched from 1990 to December 2020 to identify studies relating to treatment of isolated chronic syndesmosis injury and 17 articles were identified. We found 5 studies reporting on the results of autologous semitendinosus tendon graft in chronic syndesmosis reconstruction. We describe the case of a 47-year-old man who sustained an isolated distal tibiofibular syndesmotic injury of his right ankle that was initially missed. The patient was diagnosed at 6 months after a motocross accident and underwent reconstruction of syndesmosis with semitendinous autologous tendon associated with debridement of the fibrosous scar tissue in the anterior tibial fibular area (with preservation of the anterior sleeve) and subsequent reinsertion with transosseous stitches in the fibular bone. We used a quadricortical screw to stabilize syndesmosis definitively. After 1 month, the reduction failed because of transyndesmosic screw breakage and the patient underwent another surgery. We removed the broken screw and then used a suture button to stabilize syndesmosis permanently. The literature review and clinical case seem to suggest that reconstruction of the distal tibiofibular syndesmosis with autogenous tendon for chronic syndesmosis injury determines a good therapeutic effect in terms of both subjective symptoms and objective evaluation scores. The autologous semitendinosus tendon graft may be an appropriate and promising reconstruction target in the treatment of chronic syndesmosis injury.